The Effectiveness of Audio on learning Outcomes to Understand the Intrinsic Elements - Setiowati, Vivirian; Asmarani, Ratih; Yulianto, Bambang (Jurnal Ilmiah Sekolah Dasar, 2020)
Learning process in the school, teachers must be more innovative in the terms of storytelling. The low ability of students in understanding a story. An alternative that can increase students understanding of the ability of understanding  stories is the presence of media. Media in learning has a very important function, namely as a tool that can affect the place of learning that is being managed by the teacher. If the teacher wants to increase interest in new learning, they must use media in  learning  activities. The aim of this research is to know the effectiveness of the use of audio media in learning  understand the intrinsic elements of fairy tales on learning outcomes before and after the action on the second grade students of Elementary school of Rejoagung. This study uses a research  design model of One Group Pretest Posttest Design. By using t test statistical analysis to see the effectiveness of using audio media in learning to understand the intrinsic elements of fairy tales on learning outcomes. It can be seen in the t test in learning, there is an effective use of audio media in learning to understand the intrinsic elements of fairy tales on learning outcomes.